2016
DOI: 10.1111/cen.13283
|View full text |Cite
|
Sign up to set email alerts
|

Telomeric repeat‐containing RNA (TERRA) related to polycystic ovary syndrome (PCOS)

Abstract: We found TERRA expression in human peripheral blood leucocytes, and LTLs were positively associated with PCOS. TERRA and testosterone play an important role in the LTL regulation in PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 36 publications
(60 reference statements)
1
16
0
Order By: Relevance
“…Of the 7 studies reviewed, 3 studies showed a negative association between LTL and PCOS patients (35-37) while Wei et al demonstrated significantly longer GTL but a negative association between LTL and PCOS patients (56). Further, 1 study revealed significantly longer LTL in patients with PCOS (57). Contrastingly, Li et al demonstrated that LTL was shorter in women with PCOS and that a short LTL increased the risk of disease (58).…”
Section: Telomere Length and Female Infertilitymentioning
confidence: 89%
“…Of the 7 studies reviewed, 3 studies showed a negative association between LTL and PCOS patients (35-37) while Wei et al demonstrated significantly longer GTL but a negative association between LTL and PCOS patients (56). Further, 1 study revealed significantly longer LTL in patients with PCOS (57). Contrastingly, Li et al demonstrated that LTL was shorter in women with PCOS and that a short LTL increased the risk of disease (58).…”
Section: Telomere Length and Female Infertilitymentioning
confidence: 89%
“…The decrease in estrogen levels in postmenopausal females compared to premenopause may prevent activation of telomerase to catalyze the synthesis and extension of telomeres[39]. For the relationship between LTL and testosterone, one previous study performed by Wang et al, reported LTL were positively associated with polycystic ovary syndrome(PCOS) and indicated higher testosterone expression could promote telomere lengthening[42]. In a prospective clinical study, patients with short telomeres had an increase in telomere length in response to a pharmacologic intervention with male hormone[43].…”
Section: Discussionmentioning
confidence: 99%
“…(2017) also analyzed telomere length and TERRA levels in peripheral blood leukocytes of patients with PCOS and control subjects [96] and found that the telomeres were significantly longer in the patient-derived leukocytes [96]. Of note, the level of TERRAs, contributing to the regulation of telomere length, was found to be lower in the PCOS patients [96]. Previous studies have shown that, after aromatization, androgens may regulate telomerase expression and activity, acting through ERα [97, 98].…”
Section: Ovarian Function and Telomeres/telomerase Activity In Humansmentioning
confidence: 99%